Analysis of Consumer Satisfaction Level Towards Fresh Fish Marketing in Jakarta (Case Study at Muara Baru Modern Fish Market) - Aprianto, Hendra; Suryana, Asep Agus Handaka; Gumilar, Iwang; Gumilar, Atikah (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
As a country with a significant water area and abundant marine biodiversity, Indonesia has excellent potential in the fisheries industry, especially in providing fresh fish, a staple food for the community. The Muara Baru Modern Fish Market in North Jakarta is designed to meet this need by offering various types of fresh fish in a clean, hygienic, and modern environment. This study aims to analyze consumer satisfaction with the marketing of fresh fish in this market. Using 13 variables, including service reliability, responsiveness, assurance, empathy, tangibility, performance, features, durability, product reliability, aesthetics, perceived quality, price, and location, this study had 100 respondents selected by purposive sampling. Data analysis was carried out using the Customer Satisfaction Index (CSI), and the results showed a consumer satisfaction level of 78.75%, categorized as